Atiprimod induce apoptosis in pituitary adenoma: Endoplasmic reticulum stress and autophagy pathways - Çoker Gürkan , Ajda; Keçeoğlu, Gizem; Palavan Unsal, Narcin; ARISAN, ELİF DAMLA; ŞAHİN, BURCU AYHAN; YERLİKAYA, PINAR OBAKAN (WILEY, 111 RIVER ST, HOBOKEN 07030-5774, NJ USA, 2019)
Pituitary adenoma is the most common tumor with a high recurrence rate due to a hormone-dependent JAK/signal transducer and activator of transcriptions (STAT) signaling. Atiprimod, a novel compound belonging to the azaspirane class of cationic amphiphilic drugs, has antiproliferative, anticarcinogenic effects in multiple myeloma, breast, and hepatocellular carcinoma by blocking STAT3 activation. Therapeutic agents' efficiency depends on endoplasmic reticulum (ER) stress-autophagy regulation during drug-mediated apoptotic cell death decision. However, the molecular machinery of dose-dependent atiprimod treatment regarding ER stress-autophagy has not been investigated yet. Thus, our aim is to investigate the ER stress-autophagy axis in atiprimod-mediated apoptotic cell death in GH-secreting rat cell line (GH3) pituitary adenoma cells. Dose-dependent atiprimod treatment decreased GH3 cell viability, inhibited cell growth, and colony formation. Upregulation of Atg5, Atg12, Beclin-1 expressions, cleavage of LC-3II and formation of autophagy vacuoles were determined only after 1 mu M atiprimod exposure. In addition, atiprimod-triggered ER stress was evaluated by BiP, C/EBP-homologous protein (CHOP), p-PERK upregulation, and Ca+2 release after 1 mu M atiprimod exposure. Concomitantly, increasing concentration of atiprimod induced caspase-dependent apoptotic cell death via modulating Bcl(2) family members. Moreover, by N-acetyl cycteinc pretreatment, atiprimod triggered reactive oxygen species generation and prevented apoptotic induction. Concomitantly, dose-dependent atiprimod treatment decreased both GH and STAT3 expression in GH3 cells. In addition, overexpression of STAT3 increased atiprimod-mediated cell viability loss and apoptotic cell death through suppressing autophagy and ER stress key molecules expression profile. In conclusion, a low dose of atiprimod exposure triggers autophagy and mild-ER stress as a survival mechanism, but increased atiprimod dose induced caspase-dependent apoptotic cell death by targeting STAT3 in GH3 pituitary adenoma cells.
Keywords: Apoptotic Cell Death; Atiprimod; Autophagy; Endoplasmic Reticulum; GH3 Cells